Differences in EPG contact dynamics between voiced and voiceless lingual fricatives - Liker, Marko (Array, 2013)
Achieving voicing during fricatives is complex because voicing and frication require opposite production strategies that must be managed effectively at the supralaryngeal level. Previous research has suggested that there are differences in tongue palate contact patterns that are conditioned by voicing. However, findings have been restricted to a single time point and generally inconclusive. This study used electropalatography (EPG) to investigate differences in the dynamics of contact in voiced and voiceless lingual fricatives. Participants were 6 typically speaking Croatian adults. The speech material consisted of symmetrical VCV sequences, where C was /s z  /. EPG measures were taken throughout the fricatives and indices were used to quantify place of articulation (CoG), groove width and target configuration onset. The results showed a stable period during the central portion of the fricative. The EPG measures showed similar results for voiced and voiceless fricatives during this period. However, there were notable differences at the periphery of the fricative period ; the most significant being that the voiceless fricatives reached a stable period in terms of tongue placement and groove configuration later than the voiced fricatives. More specifically, the voiced fricatives were at their target position right at the start of frication, whereas voiceless fricatives only reached their target position at approximately a fifth of the way into the fricative. The results support aerodynamic evidence that voiced and voiceless fricatives differ in the onset and the offset of turbulence.